The Elements of Multiculturalism in Dwilogi “Angin dari Tebing” by Clara Ng. - Zulfikar Alamsyah (Anaphora : Journal of Language, Literary, and Cultural Studies, 2022)
This study discusses the values of multiculturalism contained in the dwilogi of "Angin Dari Tebing" by Clara Ng. This research aims to reveal the multiculturalism elements in Clara NG's dwilogi of “Angin Dari Tebing”. This research is based on the value theory of multiculturalism which Thobroni and Nurgiyantoro coined. The values of multiculturalism in the text are analyzed using Barthes' semiotic theory of connotation and denotation. The results of this study state that there are five values of multiculturalism contained in this dwillogi of children's stories: solidarity and brotherhood, gender equality, family values, a sense of contentment in life, and sharing and control of power. Of the five values, the values ​​of solidarity and brotherhood are described more by Clara. Each character with a different background has a high sense of tolerance and empathy so that no ethnocentrism can damage or negatively influence child readers. This study concludes that this book can be used as good reading material for children with good multiculturalism values. This book can teach about the importance of tolerance and mutual respect despite being in an environment with differences in race, ethnicity, religion, and language, as in Indonesia.